Węgry w latach 1990-2011. Polityczne, ekonomiczne i społeczne przyczyny kryzysu - Pająk-Patkowska, Beata; Patkowski, Krzysztof (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2012)
The paper attempts to answer the question of why Hungary, a country that many Western politicians praised as an exemplary model of transformation until recently, has become a European outsider, a country whose economic situation is barely better than that of Greece going bankrupt. Both political and socio-economic reasons for the crisis are indicated. The former concern the long years of living beyond their means and the cowardice of the politicians, afraid to tell their fellow citizens that sacrifices are necessary. The economic sources of the crisis concern the procrastination and non-completion of reforms that could have made Hungary a more competi tive economy. The third group of factors that contributed to the crisis was related to the condition of Hungarian society, a society that in the mid-nineteen-nineties en tered another period described as bús Magyarország , a Hungarian version of Russian smuta (trouble). A period of an upset system of values, sadness, helplessness, a sense of defeat and humiliation have led to mental and moral collapse. All this may result in Hungary’s recovery from the crisis being a very difficult and prolonged process.
Hungary in the period from 1990–2011. Political and economic sources of the crisis